Apparent pacemaker dysfunction during peptide receptor radionuclide therapy for neuroendocrine tumor. Issue 1 (14th December 2017) - Asbach, Stefan; Schluermann, Fabienne; Ruf, Juri; Bode, Christoph; Lang, Corinna
Key Clinical Message: This case is a reminder not to overlook rare causes of electrolyte shifts, which may cause reversible changes in pacemaker pacing thresholds. Abstract : This case is a reminder not to overlook rare causes of electrolyte shifts, which may cause reversible changes in pacemaker pacing thresholds.